2022
DOI: 10.1088/1755-1315/954/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the process of structure formation during ultrasonic homogenization of milk

Abstract: The article studies the processes of structure formation of milk during homogenization carried out on various equipment. A comparative analysis of the distribution of the sizes of fat globules before and after homogenization is given. The formulation of the probability mathematical model of milk and milk mixture homogenization give the opportunity to identify the real variabilities of the textural composition of milk and milk mixture in optimum performance with the use of statistics facts about dynamics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The authors of Bredikhin et al (2022b) confirm that mayonnaise is a non-Newtonian liquid and exhibits the yield stress, pseudoplasticity, and thixotropy. The authors of Bredikhin et al (2022a) indicate the pseudoplastic behavior of mayonnaise with characteristics depending on the raw material composition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of Bredikhin et al (2022b) confirm that mayonnaise is a non-Newtonian liquid and exhibits the yield stress, pseudoplasticity, and thixotropy. The authors of Bredikhin et al (2022a) indicate the pseudoplastic behavior of mayonnaise with characteristics depending on the raw material composition.…”
Section: Resultsmentioning
confidence: 99%
“…The rheological properties of mayonnaise are mainly determined by the proportion and composition of the oil phase, the presence of emulsifiers, stabilizers and thickeners (Kantekin-Erdogan et al, 2019). The quality of these products, their stability and viscosity depend on the homogenization process (Aganovic et al, 2018), the dispersion of fat droplets in the aqueous continuous phase of mayonnaise, egg yolk (Yang et al, 2020), the type of carbohydrates (Shen et al, 2011), as well as the milk component proportion and type (Saygili et al, 2022;Bredikhin et al, 2022a). Fat droplets are mechanically dispersed in the continuous aqueous phase of vinegar, and the action of a natural emulsifier from egg yolks (phospholipids, proteins) provides greater stabilization of the entire system in products of this emulsion type (Bredikhin et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Another method is mechanical homogenization, in which mixing causes particles to break (McClements et al, 2019). But another method is HIUS (Bredikhin et al, 2022). HIUS shows a significant performance in reducing the size of milk fat globules by pressure fluctuations, turbulence, and shearing (Liu et al, 2021).…”
Section: Homogenizationmentioning
confidence: 99%
“…The authors (Muadiad & Sirivongpaisal, 2022) found out that edible vegetable oil is used as the main ingredient to create this type of water-in-oil emulsion, contributing to the organoleptic and physical-and mechanical properties of mayonnaise in a specific way. The mayonnaise oil content has a significant effect on rheological properties such as yield stress, storage modulus and loss modulus (Bredikhin et al, 2022a;Yildirim et al, 2016). The use of vegetable oils different types in various combinations allows achieving the desired composition of fatty acids and tocopherols, which are natural antioxidants and can improve mayonnaise nutritional and organoleptic properties (Kostyra & Barylko-Pikielna, 2007).…”
Section: Introductionmentioning
confidence: 99%